RESPON PERTUMBUHAN DAN HASIL JAGUNG MANIS VARIETAS BONANZA DARI PEMBERIAN PUPUK BOKASHI BATANG PISANG - Syahrani, Syahrani; Fathillah, S. Syarief; Efendi, Syahrul (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2022)
This study was aimed to determine the growth and yield response of sweet corn Bonanza variety from the application of banana stem bokashi fertilizer. This research was started from April to July 2021 on Loa Tebu Village, Tenggarong District, Kutai Kartanegara Regency, East Kalimantan. This study was arranged in a non-factorial Randomized Completed Block Design (RCBD) consisting of 8 levels of treatment and 3 replications i.e. b0 (without treatment), b1 (5 t ha-1), b2 (10 t ha-1), b3 (15 t ha-1), b4 (20 t ha-1), b5 (25 t ha-1), b6 (30 t ha-1), and b7 (35 t ha-1). The results showed that banana stem bokashi fertilizer had a significant effect on the average plant height at 20 days after planting with the highest yield in treatment b4 (60.24 cm) and the lowest in treatment b3 (43.08 cm) and the average plant height 40 days after planting, with the highest yield in treatment b4 (198.92 cm) and the lowest in treatment b0 (157.58 cm). Banana stem bokashi fertilizer had no significant effect on the average plant height 60 days after planting, number of leaves, age of appearance of male flowers, weight of planting cobs and weight of cobs per hectare. The highest yield of average cob weight per hectare was in treatment b4 (33.33 ± 1.83 t ha-1) and the lowest was in treatment b0 (26.69 ± 0.29 t ha-1).